Place based preferential tax policy and its spatial effects evidence from India program on industrially backward districts. - Hasan, Rana (Economics working papers., 2017)
Place based policies aimed at enhancing economic performance of certain areas within a country or region have been popular in developed and developing countries. These policies often involve tax exemptions, subsidies, discretionary grants, special economic zones, and infrastructure support. This paper studies a typical preferential tax program that the Government of India initiated in 1994 which targeted 123 industrially backward districts in 14 states.